Multi‐hypothesis map merging with sinogram‐based PSO for multi‐robot systems. Issue 14 (1st July 2016) - Lee, H.C.; Roh, B.S.; Lee, B.H.
Abstract : Multi‐robot map merging without inter‐robot observations, common landmarks, and the knowledge of initial relative poses is a challenging problem due to lack of features or local maxima. This Letter proposes a multi‐hypothesis map merging algorithm with sinogram‐based particle swarm optimisation to solve the problem. Experimental results show that the proposed algorithm can merge individual robot maps much more accurately than the existing algorithms.